Hybridization Chain Reaction for mRNA Localization in Single Cells from Mouse and Human Cryosections. Issue 5 (25th May 2022) - May‐Zhang, Aaron A.; Benthal, Joseph T.; Southard‐Smith, E. Michelle
Abstract: In situ hybridization has been a robust method for detection of mRNA expression in whole‐mount samples or tissue sections for more than 50 years. Recent technical advances for in situ hybridization have incorporated oligo‐based probes that attain greater tissue penetration and signal amplification steps with restricted localization for visualization of specific mRNAs within single cells. One such method is third‐generation in situ hybridization chain reaction (V3HCR). Here, we report an optimized protocol for V3HCR detection of gene expression using sectioned frozen tissues from mouse and human on microscope slides. Our methods and modifications for cryosectioning, tissue fixation, and processing over a three‐day V3HCR protocol are detailed along with recommendations for aliquoting and storing V3HCR single‐stranded DNA probes and hairpin amplifiers. In addition, we describe a method for blocking background signal from lipofuscin, a highly autofluorescent material that is widespread in human neurons and often complicates imaging efforts. After testing multiple strategies for reduction of lipofuscin, we determined that application of a lipofuscin quencher dye is compatible with V3HCR, in contrast to other methods like cupric sulfate quenching or Sudan Black B blocking that cause V3HCR signal loss. This adaptation enables application of V3HCR for in situ detection of gene expression in human neuronal populations that are otherwise problematic due to lipofuscin autofluorescence. © 2022 Wiley Periodicals LLC. Basic Protocol : Mouse and human fresh‐frozen tissue in situ hybridization chain reaction on microscope slides Support Protocol : Aliquoting of HCR probes and hairpins